First records of Gastrotheca longipes (Boulenger, 1882), Cochranella resplendens (Lynch and Duellman, 1973) and Teratohyla midas (Lynch and Duellman, 1973) for the Allpahuayo-Mishana National Reserve, Peru, with comments on their distribution in the Amazon basin - Rojas Padilla, Omar (2019)
Report the first records of Gastrotheca longipes, Cochranella resplendens and Teratohyla midas in the Allpahuayo-Mishana National Reserve, Loreto region, Peru. We update the distribution maps of these three species within the Amazon basin, provide information about their natural history, and describe puffing-up body and mouth gapping behaviours in Gastrotheca longipes.